1986
DOI: 10.1159/000124615
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Central Angiotensin II Receptors with [<sup>125</sup>I]-sar<sup>1</sup>, ile<sup>8</sup>-Angiotensin II: Periventricular Sites of the Anterior Third Ventricle

Abstract: The radiolabeled angiotensin II (ANG II) antagonist, [125I]-sar1, ile8-ANG II, was used to study brain ANG II receptors by both homogenate binding and in vitro autoradiography. In homogenate preparations of the hypothalamus, thalamus, septum and midbrain (HTSM), [125I]-sar1 ile8-ANG II bound to a single class (Hill slope 0.84 ± 0.05) of high affinity binding sites (KD 0.42 ± 0.03 nM, Bmax 5.98 ± fmol/mg protein). Competitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 30 publications
(38 reference statements)
1
2
0
1
Order By: Relevance
“…The K d values obtained for [ 125 I]-Sar are in agreement with results previously reported in literature. 11,12,[15][16][17] The obtained K i values for losartan and angiotensin II also fit within the range of K i values reported in the literature. 11,[17][18][19][20] A saturation curve and displacement curve are shown in Figure 1.…”
Section: Filtration Assaysupporting
confidence: 78%
“…The K d values obtained for [ 125 I]-Sar are in agreement with results previously reported in literature. 11,12,[15][16][17] The obtained K i values for losartan and angiotensin II also fit within the range of K i values reported in the literature. 11,[17][18][19][20] A saturation curve and displacement curve are shown in Figure 1.…”
Section: Filtration Assaysupporting
confidence: 78%
“…With the development of autoradiographic methods (Mendelsohn et al, 1984;Gehlert et al, 1986;Healy et al, 1986;Saavedra et al, 1986;, it was possible to precisely determine the location of all Ang II receptors in the brain. The comparison of the distribution of brain Ang II receptors and brain Ang II immunoreactivity revealed that most of the brain Ang II, and most of the brain Ang II receptors, were localized in neurons (Lind et al, 1985;.…”
Section: Brain Angiotensin II Systemsmentioning
confidence: 99%
“…1), are present in the brain [Phillips and Sumners, 1998;Saavedra, 1992;Ganten et al, 1984]. The most convincing evidence, however, was the discovery and localization of brain Ang II receptors located inside the blood-brain barrier, inaccessible to circulating Ang II [Mendelsohn et al, 1984;Gehlert et al, 1986;Saavedra et al, 1986d;Healy et al, 1986;, and Ang II immunoreactivity [Lind et al, 1985]. Both brain Ang II receptors and brain Ang II immunoreactivity were localized in neurons Lind et al, 1985].…”
Section: Ang II Systems In the Brainmentioning
confidence: 99%